Selling Beauty Cosmetics, Commerce, and French Society, 1750-1830 - Martin, Morag (Johns Hopkins University Press, 2009)
Morag Martin's history of the cosmetic industry in France examines the evolution of popular tastes and standards of beauty during the late 18th and early 19th centuries. As the French citizenry rebelled against the excesses of the aristocracy, there was a parallel shift in consumer beauty practices. Powdered wigs, alabaster white skin, and rouged cheeks disappeared in favor of a more natural and simple style. Selling Beauty challenges expectations about past fashions and offers a unique look into consumer culture and business practices. Martin introduces readers to the social and economic world of cosmetic production and consumption, recounts criticisms against the use of cosmetics from a variety of voices, and examines how producers and retailers responded to quickly evolving fashions.Martin shows that the survival of the industry depended on its ability to find customers among the emerging working and middle classes. But the newfound popularity of cosmetics raised serious questions. Critics-from radical philosophes to medical professionals-complained that the use of cosmetics was a threat to social morals and questioned the healthfulness of products that contained arsenic, mercury, and lead. Cosmetic producers embraced these withering criticisms, though, skillfully addressing these concerns in their marketing campaigns, reassuring consumers of the moral and physical safety of their products. Rather than disappearing along with the Old Regime, the commerce of cosmetics, reimagined and redefined, flourished in the early 19th century, as political ideals and Enlightenment philosophies radically altered popular sentiment.